Indian gangsterism in Kuala Lumpur / Thevendran S Sivanantham - Thevendran S, Sivanantham (1985)
Indian gangsterism in Kuala Lumpur is a twentieth century phenomenon. Started in the 1950s as an institution to provide protection service to lower caste member it has went through numerous changes till this day, where it is scourned upon as a Criminal gang. The Indian gang sprouted through the city in the la t e 1950s and early 60s but it does not have a single line of origin Thus, we find that the various gangs differ in their rites and initiation ceremonies. These gangs are not well organized units and as such we find them constantly emerging and then dying-off. As a criminal gang, the activities of these gangs include gang fights and "table talks", vice rings, drug pushing, extortion and "protection service". For these purposes, the gangs use a wide range of weapons, from meat choppers to revolvers. The role of' the police in curbing the increasing menace of these gangs basal so increased lately. The fear that these gangs create and the atrocious activities that they involve in has brought about tighter legislation against them. The emergence of "gangster- type" individuals is linked closely to the social environment o£ an individual. It is found that these gangsters who come from lower class communities go through detective socialization processes that create delinquent. Various factors contribute towards this cause, namely, broken homes, lack of parental love and control, bad neighbourhood and influence of friends. Indian gangs although have not adapted themselves well to the social changes, they still pose a threat to the safety of the general public and as such it is very necessary to check their growth. While legislation is important in this aspect, of more importance is to help children and youths to go through normal and proper socialization process to avoid the emergence of delinquent features in the first place.